Estratégias para a remoção de pigmentos depositados sobre bráquetes estéticos - Otero, Laura Meireles (2016)
The aim of this study was to evaluate the efficiency of cleaning methods in removing pigment deposited on aesthetic brackets, after immersion in coffee. We selected 160 premolar brackets (80 monocrystalline and polycrystalline 80). The brackets were fixed on a glass blade and soon, thereafter, color measurement was performed using a spectrophotometer (T0). For each means of immersion, 80 brackets were selected (40 for each type of ceramic). Soon after staining (30 days of immersion), new color measurements were made (T1). Subsequently, the specimens were divided randomly into four groups for brushing, bleaching, blasting with sodium bicarbonate jet and sodium bicarbonate jet followed by bleaching. New color measurements were made after each cleaning method was used (T2). The color change of the brackets was evaluated according to two formulae, i.e., CIELAB and CIEDE2000. The differences between the average ΔE according to treatment, bracket, and solution were evaluated by linear regression analysis. The greatest staining was caused by coffee. The crystalline structure did not influence the color change. The methods with lower averages of ΔE for coffee were sodium bicarbonate jet followed by bleaching and bleaching, followed by the group that received brushing and sodium bicarbonate jet (both CIELAB as to CIEDE2000). The CIEDE2000 formula was more sensitive in detecting non-acceptable and perceptible differences in color when compared with the CIELAB formula. It was concluded that the most effective methods to remove pigment deposited on aesthetic brackets are sodium bicarbonate jet followed by bleaching and bleaching alone.